"I had so many feet in so many camps". Interview with Jan Kregel - Jan Kregel (Intervention. European Journal of Economics and Economic Policies, 2008)
First paragraph: In your career you have worked with different leading Post-Keynesians, like Joan Robinson, Alfred Eichner, Nicholas Kaldor or Paul Davidson, who was a PhD adviser of yours. What was their main impact on your work and are there any other teachers who impressed you or were important for you?
Keywords: 330